Exploring Qualities Present in Current Versus Dissolved Cross-Group Friendships - Elena Buliga; Phuong Nguyen; Cara C. MacInnis (Social Psychological Bulletin, 2020)
In general, cross-group friendships are less stable than same-group friendships. What conditions are present in currently existing versus dissolved cross-group friendships? In order to examine qualities that may influence cross-group friendship stability we compared current and dissolved friendships, including cross-group friendships. Cross-group friendships exist in various group domains, some more easily categorizable than others. That is, sometimes it is easy to tell that a relationship is cross-group (e.g., cross-race), and other times this is less clear (e.g., cross-socio-economic status). Thus, we compared current and dissolved friendships across both a more and a less easily categorizable group domain. In this study, participants reported on their current and dissolved friendships, and we found that, overall, friendship influencing qualities such as closeness, similarity, and social network integration (i.e., becoming friends with the friends of one’s own friends) were present to a greater extent in current versus dissolved friendships. This was the case for both cross-group and same-group friendships. These qualities may influence cross-group friendship stability.